2004
DOI: 10.1093/mutage/geh028
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei induced by aneugens and clastogens in mononucleate and binucleate cells using the cytokinesis block assay

Abstract: The human in vitro micronucleus (MN) test has become a fast and reliable assay for mutagenicity testing. Currently, this assay is mostly performed with cytochalasin B, which prevents cytokinesis, resulting in polynucleated cells. The number of nuclei per cell indicates the number of nuclear divisions that have occurred since the addition of cytochalasin B. It is recommended that MN are only counted in binucleated lymphocytes, because these cells have finished one nuclear division. Therefore, almost no attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 48 publications
3
35
0
2
Order By: Relevance
“…It induced an extremely high number of MN in mononucleated as well as in binucleated cells in human, indicating an aneugenic action. This was confirmed by cytokinesis block micronucleus assay (Rosefort et al 2004).…”
Section: Discussionmentioning
confidence: 55%
“…It induced an extremely high number of MN in mononucleated as well as in binucleated cells in human, indicating an aneugenic action. This was confirmed by cytokinesis block micronucleus assay (Rosefort et al 2004).…”
Section: Discussionmentioning
confidence: 55%
“…The frequency of MNi and NBUDs in non-divided mononuclear cells can also be scored if the level of pre-existing DNA damage needs to be measured; however, this approach cannot be used instead of the CBMN Cyt assay, because it does not account for DNA damage accumulated in the bulk of lymphocytes in vivo while circulating in the quiescent phase, it cannot be used to measure NPBs and does not give the same results as scoring MN and NBUDs in BN cells 3,90,91,97 .…”
Section: Box 2 | Examination Of Slides and Slide Scoring For Assessmementioning
confidence: 99%
“…In the case of lymphocytes, it would be preferable to delay the start of the treatment phase to 48 h after mitogen stimulation at which point a large proportion of the mitogen-activated cells would have progressed from G1 to S, G2 and M phases of the cell cycle. By scoring MN in both mononucleated and BN cells, it should be possible to account for MN expressed before Cyt-B block as well as cells with MN that fail to divide and cells that undergo mitotic slippage 91,97 . The suggested protocol also allows for harvesting of cells at the end of the treatment phase before Cyt-B addition if there is a need to test whether the chemical inhibits cytokinesis.…”
Section: Other Primary Cell Culturesmentioning
confidence: 99%
“…The slides were coded at the time of preparation and scoring. The frequency of MN was determined in 2000 BN and in 2000 MO lymphocytes per culture [18,21,28,40]. The slides were analyzed using a Carl Zeiss â microscope with an X400 objective.…”
Section: Control Exposedmentioning
confidence: 99%
“…However, it was observed that MN in mononucleated (MO) cells, as well as proliferative index (PI), could provide complementary information, since these data may indicate damage that is present in vivo, before cell culture is set up, which makes them interesting for the purpose of biomonitoring [28,40].…”
Section: Introductionmentioning
confidence: 99%